Incorporating patient experience into drug development for ulcerative colitis: development of the Urgency Numeric Rating Scale, a patient-reported outcome measure to assess bowel urgency in adults - Marla C. Dubinsky; Peter M. Irving; Remo Panaccione; April N. Naegeli; Alison Potts-Bleakman; Vipin Arora; Mingyang Shan; Simon Travis (SpringerOpen, 2022)
Abstract Background Bowel urgency, the sudden or immediate need to have a bowel movement, is a common, bothersome and disruptive symptom of ulcerative colitis (UC). UC treatment goals include control of urgency; however, it is not consistently assessed in UC clinical trials. The Urgency Numeric Rating Scale (NRS) is a new patient-reported measure to assess severity of bowel urgency in adults with UC developed in accordance with Food and Drug Administration guidelines. Methods Qualitative interviews were used to develop Urgency NRS. The scale asks patients to report the immediacy status of their UC symptom over the past 24 h on an 11-point horizontal numeric rating scale [0 (No urgency) to 10 (Worst possible urgency)]. Higher scores indicate worse urgency severity. A 2-week diary study assessed floor and ceiling effects, test-retest reliability (intraclass correlation coefficient (ICC) (2,1) between Week 1 and 2), and construct validity (Spearman correlation using Week 1 scores). Weekly scores were calculated as mean score over each 7-day period. Results Qualitative interviews with 16 UC patients (mean age 37.9 ± 11.6 years; 50% female; 56% White) confirmed relevance, content, and comprehensiveness. The 2-week diary study included 41 UC patients (mean age 44.2 ± 14.6 years; 51% female; 56% White). No ceiling or floor effects were identified. Test-retest reliability was high (ICC = 0.877). Average Urgency NRS and patient global rating of severity scores were highly correlated, with a moderate correlation between average Urgency NRS and stool frequency, demonstrating construct validity. Conclusions Bowel urgency is a distinct symptom of UC. The Urgency NRS is a well-defined, content-valid, and reliable measurement of bowel urgency in adults with UC.